2020
DOI: 10.1038/s41375-020-0962-2
|View full text |Cite
|
Sign up to set email alerts
|

The mevalonate pathway is an actionable vulnerability of t(4;14)-positive multiple myeloma

Abstract: Multiple myeloma (MM) is a plasma cell malignancy that is often driven by chromosomal translocations. In particular, patients with t(4;14)-positive disease have worse prognosis compared to other MM subtypes. Herein, we demonstrated that t(4;14)-positive cells are highly dependent on the mevalonate (MVA) pathway for survival. Moreover, we showed that this metabolic vulnerability is immediately actionable, as inhibiting the MVA pathway with a statin preferentially induced apoptosis in t(4;14)-positive cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…To date, there is one account in the literature that evaluates the benefit of combining IBP pathway inhibitors with PI therapy. This study shows that statins, which inhibit HMG-CoA reductase in the mevalonate pathway and lead to downstream disruption in isoprenoid synthesis, enhanced induction of apoptosis and UPR markers when used in combination with bortezomib in t (4;14)-positive MM cells [ 40 ]. Furthermore, using add-back studies they demonstrate that GGPP depletion drives apoptosis and UPR activation in their model.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is one account in the literature that evaluates the benefit of combining IBP pathway inhibitors with PI therapy. This study shows that statins, which inhibit HMG-CoA reductase in the mevalonate pathway and lead to downstream disruption in isoprenoid synthesis, enhanced induction of apoptosis and UPR markers when used in combination with bortezomib in t (4;14)-positive MM cells [ 40 ]. Furthermore, using add-back studies they demonstrate that GGPP depletion drives apoptosis and UPR activation in their model.…”
Section: Discussionmentioning
confidence: 99%
“…Next to fatty acid synthesis, the mevalonate pathway was also implicated in t(4;14) MM. It was demonstrated that inhibition of the rate-limiting enzyme HMGCR by statin treatment is preferentially toxic to t(4;14) MM cells [ 221 ]. Inhibition of HMGCR through fluvastatin activated the integrated stress response (ISR), a stress response induced by ER stress and nutrient deprivation, amongst other things.…”
Section: Fgfr3 Deregulation In MMmentioning
confidence: 99%
“…Many small GTPases, such as Ras and Rho, as members of the Ras superfamily of small GTPases involved in tumorigenesis, must be isoprenylated (25). Therefore, inhibiting the mevalonate pathway can reduce the isoprenylation of small GTPases, thereby inducing cancer cell death (26)(27)(28). In contrast, uncontrolled flux of mevalonate pathway metabolites promotes sustained Ras protein activation by constitutive prenylation, triggering malignant transformation (13).…”
Section: Discussionmentioning
confidence: 99%